Nature of Atrazine (2-Chloro-4-ethylamino-6- isopropylamino-s-triazine )-Copper Chloride Complex. - ARORA, C.L.; SEKHON, G.S. (Asian Journal of Chemistry, 2010)
Treatment of atrazine (2-chloro-4-ethylamino-6-isopropylamino-s-triazine) with anhydrous copper chloride in methanol yields 1 : 1 complex. The infrared spectra and n.m.r. spectra do not suggest coordination of the nitrogen atoms of the side chain or C3N3 ring with the metal atom; instead a bond between the π-electrons of the C3N3 ring and the metal atom is indicated from the far IR spectra of this complex.